Investigation into the PSD characteristics of internally unstable soils susceptible to suffosion - Xingjie Zhang; Ahmed Benamar; Linjun Yang; Jun Zhu; Mohamad Oueidat; Yulong Luo (Scientific Reports)
Abstract Internal instability of embankment soils under seepage can occur in two distinct ways: suffusion and suffosion. Suffusion involves the removal of fine particles from the matrix without causing significant disturbance to the soil skeleton, while suffosion is characterized by the movement of fine particles accompanied by skeleton collapse or deformation. In terms of dam safety, suffosion poses a greater threat than suffusion. While extensive research has focused on establishing geometric criteria to assess the internal instability of soils prone to suffusion, current criteria fail to predict the occurrence of suffosion. To address this gap, this paper presents a comprehensive analysis by collecting a large amount of experimental data from existing literature, as well as conducting a series of suffusion/suffosion tests. Through this analysis, two characteristic parameters have been identified: fines content (F f ) and the retention ratio (D’ 15/d’ 85) which represents the relationship between coarse and fine particles. Soils including fines content greater than 35% are susceptible to suffosion, while soils with fines content lower than 20% are prone to suffusion. For soils with fines content ranging between 20 and 35%, suffosion occurs when F f > 2.73 D’ 15/d’ 85 + 0.89. These findings provide valuable insights for future analyses of soil internal stability and contribute to enhancing dam safety. The combination of literature data and suffusion tests offers a robust base for assessing the risk of suffosion and suffusion in soils, allowing more accurate evaluation of soil behavior and effective mitigation strategies in dam engineering.